Shear behaviour of self compacting concrete beams reinforced with palm kernel fibre - Obeng, Jacqueline (2017)
A thesis submitted to the Department of Civil Engineering College of Engineering in partial fulfilment of the requirements for the degree of Master of Science, 2016